Management of the Management Strategy of the Giwangan Traditional Main Market by the Special Region Government of Yogyakarta - Lesmana, Meichio; Fratama, Akbar Zulfia; Rosmitha, Siti Nurma; Suminto, Ahmad (INOVATOR, 2024)
Government management and strategy in managing traditional markets is very necessary, seeing the conditions of traditional markets which if not considered, will have an impact and reduce public interest in conducting transactions in traditional markets due to the influence of modern markets. The purpose of this study was to describe the management strategy of the Giwangan wholesale market by the government of the Special Region of Yogyakarta (DIY). This type of research uses descriptive-qualitative with a SWOT analysis approach. The data used are primary data obtained through observation, interview, observation, Focus Group Discussion (FGD) and documentation. This study also uses a phenomenological approach to case studies. The results showed that the implementation carried out by the government of the Special Region of Yogyakarta in the management of the Giwangan traditional wholesale market was quite effective, namely the implementation of several market management programs in terms of planning, structuring, organizing, field action, as well as monitoring and evaluation. In market management, the DKI government takes a two-way approach. First, an infrastructure approach with infrastructure improvements and additions, a program to rearrange market conditions in 2022, greeting traders once a week, gotong royong with associations, and exercising with market traders. Second, the non-physical approach is the application of regional regulations and mayoral regulations. This has an impact on the welfare of the people of Yogyakarta.